Coping with Oil Price Volatility - Bacon, Robert; Kojima, Masami (World Bank, Washington, DC, 2014)
Oil is important in every economy; when its prices are high and volatile, governments feel compelled to intervene. Because there can be large costs associated with such interventions, reserve banks, central planning institutions, and think tanks in industrial countries have been carrying out quantitative analyses of oil price volatility for a number of years. This report focuses on fluctuations around trends in oil prices. It examines measurements of oil price volatility and evaluates several different approaches to coping with oil price volatility: hedging, security stocks, price-smoothing schemes, and reducing dependence on oil including diversification. It does not deal with the impact of oil price volatility on countries' macroeconomic performance or with macroeconomic policy responses; these generally have more to do with coping with higher price levels than with higher volatility per se. The study examines oil price volatility largely from the point of view of consumers and does not cover the management of revenue volatility by large oil exporters.